Asuhan Keperawatan Keluarga Pada Ny. S Dengan Gout Arthritis: Studi Kasus Di Dukuh Karanganyar Desa Tonjong Kabupaten Brebes - Putri Anggraeni; Ahmad Zakiudin (STIKES Columbia Asia Medan, 2026)
Background: Gout arthritis is a metabolic disease caused by excessive uric acid levels in the blood (hyperuricemia), which leads to monosodium urate crystal deposition in the joints. Globally, the prevalence of gout arthritis ranges from 1–4% of the general population. In Indonesia, the national prevalence reaches approximately 7.3% based on medical diagnosis, and in Brebes Regency, cases reach 62.4%. At the Tonjong Health Center service area, the prevalence of gout arthritis in Karanganyar Hamlet, Tonjong Village, reaches 2.04%. Gout arthritis requires comprehensive nursing care including pain management and health education to prevent recurrence. Objective: To implement nursing care for Ny. S, family of Tn. S, with musculoskeletal system disorder: gout arthritis in Karanganyar Hamlet, Tonjong Village, Tonjong District, Brebes Regency. Method: This study used a case study design with a single patient/family subject. Data collection was conducted through interview, observation, physical examination, and study documentation on December 26–27, 2025 at the patient's home. Results: Assessment revealed Ny. S (72 years) experienced acute pain in the right knee joint with a pain scale of 3/10 and uric acid level of 7.3 mg/dL, along with knowledge deficit regarding gout arthritis. Two nursing diagnoses were established: acute pain and knowledge deficit. Nursing interventions included pain management education, non-pharmacological therapy (turmeric decoction), pharmacological therapy (allopurinol), and health education. Implementation was conducted over two visits. Evaluation results showed that acute pain was partially resolved (pain scale reduced to 2/10, uric acid 7.2 mg/dL) and knowledge deficit was resolved. Conclusion: Nursing care for patients with gout arthritis through pain management and health education can reduce pain intensity and improve family knowledge about the disease. Non-pharmacological intervention with turmeric decoction contributed to decreasing uric acid levels and pain. Keywords: gout arthritis, acute pain, knowledge deficit, family nursing care, non-pharmacological therapy